If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(t + 3) + -5 = 1 Reorder the terms: 6(3 + t) + -5 = 1 (3 * 6 + t * 6) + -5 = 1 (18 + 6t) + -5 = 1 Reorder the terms: 18 + -5 + 6t = 1 Combine like terms: 18 + -5 = 13 13 + 6t = 1 Solving 13 + 6t = 1 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 6t = 1 + -13 Combine like terms: 13 + -13 = 0 0 + 6t = 1 + -13 6t = 1 + -13 Combine like terms: 1 + -13 = -12 6t = -12 Divide each side by '6'. t = -2 Simplifying t = -2
| (u+1)(u-6)= | | 5(18-x)=9(4x-32) | | 6.1x-3+x-1.2= | | 12-2X+3X=-3-2 | | -2=1+C | | spx-7=2px+2 | | 2=B-6 | | 4927=n/15 | | .6666y+4=2x | | 3=-11+A | | m-9m-m+9= | | y-36=-28 | | 5/x+8/3x^2 | | 3xy+3yx= | | mx+25=-36 | | f=73905/15 | | 3xy=3yx | | m+7m-3m+4= | | X^2-8=3 | | 73905=n/15 | | V=3.14R2h/3 | | -3/2(1) | | -2-2w+2=2-7w+2 | | m-2m-8m+7= | | 0=-2x^2+6x | | (2xy)(5xy)= | | 5x+85-53/2x=51 | | 32x^2+12x+1= | | 12y^2(y/3+9x/y2)=4y^3-72 | | 4z-3(z+1)=2(z-3)-z | | 11/6/(-8) | | 49x^2-14x-48= |